L'égalité selon la Cour suprême - Bourque, Denis (Les Cahiers de droit, 1977)
Clause 1(b) of the Canadian Bill of Rights specifies that every person has the right to equality before the law. The purpose of this article is to analyse, on the one hand, the meaning that the judges of the Supreme Court have given to this concept of equality before the law and, on the other hand, the way in which they have applied this aforementioned principle of Clause 1(b) of the Canadian Bill of Rights.Four judgements are the subject of Mr. Bourque's study. He concerns himself with the Drybones, Lavell, Burnshine and Canard judgements. In the course of analysing these cases, Mr. Bourque brings out the shilly-shallying of the judges in connection with their concept of equality before the law. In spite of this beating about the bush two concepts emerge at the level of the judges of the Supreme Court, namely an equalitarian concept of equality before the law, and a concept which makes equivalent equality before the law and the rule of law. According to Mr. Bourque, the analysis of these four judgements shows that it is the concept which makes equivalent equality before the law and the rule of law, which represents, the position of the Supreme Court, at the present time.